Examining the self-regulated learning scale using the Rasch model approach - Nizaruddin, Nizaruddin; Muhtarom, Muhtarom; Murtianto, Yanuar Hery; Sutrisno, Sutrisno (Universitas Islam Negeri Raden Intan Lampung, 2024)
Self-regulated learning is a crucial aspect of the learning process for students. This ability is often overlooked due to the challenges of inaccurate measurement. This study aims to evaluate the quality of a self-regulated learning scale developed through an analysis of respondent responses. The research employed a descriptive quantitative approach using the Rasch Model as the analytical method. The instrument used consisted of 30 statement items. The study sample included 59 mathematics education students selected through cluster random sampling from two universities in different districts. The analysis results indicated that, after three calibration processes, the self-regulated learning scale was refined to 28 items with excellent quality. Furthermore, the responses of 58 students demonstrated a high level of consistency. Thus, self-regulated learning scale has good validity and reliability, making it a dependable tool for measuring self-regulated learning abilities. The implications of this study include the provision of a practical and reliable instrument for researchers and educators to support further studies and serve as an evaluation tool in learning development.